2014
DOI: 10.1111/risa.12164
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting MSHA Citations Through the Lens of Occupational Health and Safety Management Systems: Investigating Their Impact on Mine Injuries and Illnesses 2003–2010

Abstract: Since the late 1980s, the U.S. Department of Labor has considered regulating a systems approach to occupational health and safety management. Recently, a health and safety management systems (HSMS) standard has returned to the regulatory agenda of both the Occupational Safety and Health Administration (OSHA) and the Mine Safety and Health Administration (MSHA). Because a mandated standard has implications for both industry and regulating bodies alike, it is imperative to gain a greater understanding of the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
(47 reference statements)
0
14
0
1
Order By: Relevance
“…Previous ratio research has not explicitly included a consideration of generalizability in relation to organizational size. Consistent with previous studies that model the impact of predictor variables on OSH incidents over time, (1,15,26) it appears relevant to include a multiple logistic regression model that controls for the consideration that an increased number of hours worked during the year at a given establishment can influence the probability for a fatal event to occur within the same establishment. However, given that mine size is also likely to influence the lower severity OSH incident predictors (perhaps unequally), its inclusion as a control could act as a suppressor variable and impact the ability to adequately interpret their relative effects.…”
Section: Analytical Approachmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous ratio research has not explicitly included a consideration of generalizability in relation to organizational size. Consistent with previous studies that model the impact of predictor variables on OSH incidents over time, (1,15,26) it appears relevant to include a multiple logistic regression model that controls for the consideration that an increased number of hours worked during the year at a given establishment can influence the probability for a fatal event to occur within the same establishment. However, given that mine size is also likely to influence the lower severity OSH incident predictors (perhaps unequally), its inclusion as a control could act as a suppressor variable and impact the ability to adequately interpret their relative effects.…”
Section: Analytical Approachmentioning
confidence: 86%
“…As a result, each OSH incident in the AII database was classified as: (1) a fatality; (2) an injury that resulted in a permanent disability; (3) an injury that resulted in lost and/or restricted days (herein referred to as a days lost injury); (4) an injury that resulted in medical treatment beyond first aid, but did not result in death, days away, or restricted duty/job transfer (herein referred to as a reportable injury); and (5) a reportable incident that did not result in an injury (herein referred to as a reportable noninjury). 1 Dummy variables were created for each of the degree categories and each reported OSH incident was then coded within the AII database. We also reserved the variables pertaining to lost and restricted days per incident for subsequent analysis related to research question number 3.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Research is required to identify technology enablers that inspectors could use to help them succeed fully, and research is needed improve inspection protocols. Another productive line of inquiry would be to examine MSHA's ''investment'' in a mix of enforcement activities, using similar methods to those for examining the value of a company's investment in a mix of safety and health activities (for example, see [4]). Do each of their enforcement activities yield a measurable benefit, or are some activities more directly correlated with positive safety and health gains?…”
Section: Revolutionary Advancementsmentioning
confidence: 99%
“…Previous research has shown that analyzing MSHA citations can offer insight into practices that companies and their health and safety leadership can use to improve mineworker health and safety (Yorio, Willmer and Haight, 2014). In their study, Yorio, Willmer and Haight analyzed MSHA citations through a health and safety management system lens to determine the impact on subsequent-year mine-level injuries and illnesses.…”
Section: Introductionmentioning
confidence: 99%